Dual‐emissive polydiphenylsilane nanocomposite: effect of N, N′‐bis(4‐hydroxysalicylidene)‐1, 2‐phenylenediamine‐Zn complex. (19th July 2015) - Sacarescu, Liviu; Cojocaru, Corneliu; Ardeleanu, Rodinel; Fortuna, Maria; Sacarescu, Gabriela; Simionescu, Mihaela
Abstract : The fluorescence properties of polysilane can be strongly influenced by creating new excited states that involve electronic transitions and the relaxation to the ground state. This work presents the optical effects obtained by doping a specially designed polydiphenylsilane copolymer with Zn complex of N, N ′‐bis(4‐hydroxysalicylidene)‐1, 2‐phenylenediamine. The nanocomposites have been prepared in solution by mixing the polymer with low amounts of Zn–salophen and using tetrahydrofuran as solvent. The ultraviolet–visible spectrum has shown the occurrence of an intermolecular charge transfer between polysilane and the metal complex. Photoluminescence studies have revealed an interesting dual emission profile of nanocomposite. The origin of this phenomenon has been evidenced by molecular modeling and simulation of the electronic transitions. The modeling results have unveiled a new low‐lying excited state due to intermolecular interactions. The thin films of nanocomposites have been drop‐casted from solutions. The obtained films have been studied by Transmission Electron Microscopy (TEM)‐Scanning Transmission Electron Microscopy (STEM)‐Energy Dispersive X‐ray analysis (EDX) to gain information on the film‐forming capacity and surface morphology. The results have revealed a high potential of such materials for fluorescence sensing applications. Copyright © 2015 John Wiley & Sons, Ltd.